Synthesis of Pd0.01FexCe(1−x)/2Zr(1−x)/2Oy catalysts and their catalytic performance for ammonia production by passive SCR reaction. (2nd March 2021) - Liu, Min; Yan, Ruining; Zhao, Xuteng; Wang, Yinan; Zhan, Reggie; Lin, He
Abstract : The passive ammonia SCR system has been considered as a novel after-treatment method to reduce the emission of NO x and produce ammonia for downstream SCR. Abstract : The passive ammonia SCR system has been considered as a novel after-treatment method to reduce the emission of NO x and produce ammonia for downstream SCR. A series of Pd0.01 Fe x Ce(1− x )/2 Zr(1− x )/2 O y catalysts ( x = 0, 0.1, 0.2, and 0.4) was synthesized through a solution combustion synthesis (SHS) method. Their catalytic activities were investigated by XRD, BET, Raman, H2 -TPR, XPS, and in situ DRIFTS. The relationship between the reactivity and species composition, acidic properties, surface oxygen vacancies, and redox behavior of the Pd0.01 Fe x Ce(1− x )/2 Zr(1− x )/2 O y catalysts was established. Results demonstrated that a moderate amount of Fe doping can markedly enhance the specific surface area, improve the surface oxygen vacancies, increase the surface acidic sites, and tune the valence distribution of surface elements. Pd0.01 Fe0.1 Ce0.45 Zr0.45 O x showed the highest ammonia yield with a wide reaction-temperature window (250–400 °C) and >95% NO conversion and complete conversion from nitric oxide to ammonia at 300–400 °C. This may be due to the phenomenon that highly dispersed Fe2 O3 enhanced the interaction among PdO, Fe2 O3 and the Ce0.5 Zr0.5 O2 support, improved the displacement of active species on the catalyst surface, and increased the surface oxygen vacancies, thus improving the catalytic activity.